Rise in protectionism : trade and payments division (Washington, 1978)
In contrast to the extensive pattern of trade barriers erected in the 1930s, the postwar period was, generally, one of progressive movement toward a liberal world trading system. This process, which began with the series of conferences convened in 1944-48 at the initiative of the United States, culminated in the coming into force of the General Agree ment on Tariffs and Trade (GATT). The GATT was based on the premise that international cooperation, an agreed code of conduct, and a stable framework were essential to prevent the pursuit of narrow national interests that would lead to the escalation of trade restrictions and eventually to a decline in the volume of trade, and it represented a major step toward replacing the severely constrained trade relations character istic of the interwar period with a system founded on reciprocity and nondiscrimination, a set of ground rules for international trade, and a mechanism for further trade liberalization.
Keywords: Financial economics